Student Attitudes Toward AI-Assisted Thesis Writing and Critical Reading: A Case Study from Indonesian English Programs - Wahyu; Uswatun Hasanah; Muhammad Arifin Muhkam; Purwati, Dewi (STAIN Majene, 2025)
This study explores the role of Artificial Intelligence (AI) in undergraduate thesis writing within English Language Education programs in Indonesia, particularly its influence on students' academic writing and critical reading. Using a qualitative case study approach, the research investigates how final-year students incorporate AI tools such as ChatGPT, Quillbot, and Claude AI throughout the thesis development process, including research, drafting, revision, and engagement with academic texts. Data were collected through semi-structured interviews involving twelve students who had experience using AI during their thesis work. Findings show that students perceive AI as a helpful tool for improving writing structure, grammar, and argumentation. Beyond writing support, AI was also seen as valuable for enhancing reading comprehension, especially in interpreting complex academic texts, clarifying unfamiliar concepts, and synthesizing multiple sources. However, they expressed concerns about the risk of over-reliance on AI, particularly when it replaces deep reading or independent thinking. These insights highlight both the benefits and limitations of AI in academic context. The study concludes that while AI tools can support academic literacy by enhancing both writing and reading practices, their effectiveness depends on how they are used. Thoughtful integration of AI in higher education should promote ethical awareness, reflective use, and the continued development of essential skills such as critical thinking, critical reading, and independent writing.